2009
DOI: 10.1117/1.3210781
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of reflected light intensity changes during navigation and radio-frequency lesioning in the brain

Abstract: An electrode with adjacent optical fibers for measurements during navigation and radio frequency lesioning in the brain was modeled for Monte Carlo simulations of light transport in brain tissue. Relative reflected light intensity at 780 nm, I 780 , from this electrode and probes with identical fiber configuration were simulated using the intensity from native white matter as reference. Models were made of homogeneous native and coagulated gray, thalamus, and white matter as well as blood. Dual layer models, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Other public MC code are available for the simulation of photon transport Monte Carlo multi layered (MCML), MCextreme or tMCimg [26,42,43], but do not allow to simulate thermal effects simultaneously. MCML has been used to simulate the transport and detection of photons in the context of brain neurosurgery for the safe and accurate positioning of electrodes [44] and is limited to semi-infinite layer geometries. tMCimg and MCextreme allow to simulate more realistic geometries based on segmented MRI or CT images but require data to be formatted into meshed files, which are not straightforward to handle for neurobiologists or neurosurgeons.…”
Section: What Are the Limitations Of The MC Simulations?mentioning
confidence: 99%
“…Other public MC code are available for the simulation of photon transport Monte Carlo multi layered (MCML), MCextreme or tMCimg [26,42,43], but do not allow to simulate thermal effects simultaneously. MCML has been used to simulate the transport and detection of photons in the context of brain neurosurgery for the safe and accurate positioning of electrodes [44] and is limited to semi-infinite layer geometries. tMCimg and MCextreme allow to simulate more realistic geometries based on segmented MRI or CT images but require data to be formatted into meshed files, which are not straightforward to handle for neurobiologists or neurosurgeons.…”
Section: What Are the Limitations Of The MC Simulations?mentioning
confidence: 99%
“…Qian and colleagues [101] studied the "look ahead distance" in brain matter by means of Monte Carlo simulation and found that in the near infrared region and for small fiber separation, grey matter is expected to have a slightly increased "look ahead distance" than white matter. This was confirmed by Johansson et al [59]. Nevertheless, the optical resolution is higher than the resolution in a 1.5 Tesla MRI system where imaging is done with 2 mm trans-axial slices.…”
Section: Optical Intracerebral Measurementsmentioning
confidence: 55%
“…In general, the light interaction with tissue, and thus the measurement depth, is affected by several aspects such as probe design, light source and the tissue's scattering and absorption characteristics. Experimental investigations and Monte Carlo simulations show that the optical sampling depth in brain tissue is less than 1 mm [59,71,101]. Qian and colleagues [101] studied the "look ahead distance" in brain matter by means of Monte Carlo simulation and found that in the near infrared region and for small fiber separation, grey matter is expected to have a slightly increased "look ahead distance" than white matter.…”
Section: Optical Intracerebral Measurementsmentioning
confidence: 99%
“…The fibre distances were kept the same resulting in similar sampling volumes. Previous studies based on Monte Carlo simulations using similar optical probe tip designs have estimated the optical sampling depth to approximately 1 mm in brain tissue [16,9,18]. The probe design could also be compared with previous investigations where a subdural optode-strip was used on the brain surface [7,35].…”
Section: Discussionmentioning
confidence: 96%